The Effect of Asymmetric Information, Board of Commissioners Size, and Independent Board of Commissioners, on Earnings Management with Managerial Ownership as a Moderating Variable - Pratiwi, Diah Ajeng; Saputra, Dian (GoAcademica Research & Publishing, 2024)
The tendency of company’s always wants to maximize their profits, which makes earnings management practice often carried out by management. This research aims to examine and get empirical evidence related to the effect of asymmetric information, board of commissioner size, and independent board of commissioners on earnings management with the ownership of the managers as a moderating variable. This research has been carried out on real estate and real estate related companies listed on the Indonesian Stock Exchange in 2020-2022. Data type is secondary data in the form of audited accounts. Structural Equation Modeling-Partial Least Square (SEM-PLS) is the data analysis method used. The findings indicated that asymmetric information, board of commissioner size and independent board of commissioners had no effect on earnings management. However, after managerial ownership becomes a moderating variable, independent board of commissioners has an effect on earnings management.